Comparative Study of Influence of Cryopreservation Regimens on Free and Immobilized Cells of Saccharomyces boulardii Probiotic - Vysekantsev, I. P.; Babinets, O. M.; Martsenyuk, V. F.; Gurina, T. M. (Problems of Cryobiology and Cryomedicine, 2024)
The influence of cooling regimens and preserving media composition on Saccharomyces boulardii probiotic free cells and those immobilized on enterosorbents, was comparatively studied. The preservation of higher viability of free yeast cells was established after application of all the cryopreservation regimens. The viability of ‘carrier-cells’ complexes was much lower. Cooling with 1 degree/min rate provided the maximum viability for free and immobilized cells.